Art labor, sex politics : feminist effects in 1970s British art and performance - Wilson, Siona (University of Minnesota Press, 2016)
Contrary to critics who have called it the 'undecade', the 1970s were a time of risky, innovative art - and nowhere more so than in Britain, where the forces of feminism and labour politics merged in a radical new aesthetic. In 'Art Labor, Sex Politics', Siona Wilson investigates the charged relationship of sex and labour politics as it played out in the making of feminist art in 1970s Britain.